DINAMIKA KEPUASAN PERNIKAHAN PADA ISTRI YANG DIJODOKAN DALAM KELUARGA KIAI - Merzavani, Ayu (University of Surabaya, 2016)
Marital satisfaction is something achieveable, one of them by having sufficient introductory period. This one is not experienced by the paired couple, including in a parit of Islamic society: family of Kiai. Accordingly, this research was conducted to uncover the dynamics of marital satisfaction on the wife who married through arranged marriage in the family of Kiai. As a result, subjects satisfied with their marriage. The easiest aspects which is achieved is religious orientation included in the psychological needs. It is influenced by the same interests and values in terms of religion. While aspect that is still not fully bringing satisfaction is effective communication, which is a shortage of an arranged marriage. Satisfaction achieved at this stage of the family with young children is based on the autonomy and relationships with students which only occurs in paired wife within the family of Kiai.